Divergence in Potential Contact Pheromones and Genital Morphology Among Sympatric Song Types of the Bush Cricket Mecopoda elongata - Dutta, Rochishnu; Balakrishnan, Rohini; Tregenza, Tom (Frontiers in Ecology and Evolution, 2018)
A well-established route to speciation in animals is via the evolution of divergent male mating signals and female preferences within a species. However, an open question is how common it is for near complete isolation to be achieved through a single signal-receiver system or whether multiple aspects of the mate-recognition system diverge simultaneously. The five highly divergent song types of the bush cricket Mecopoda elongata, exemplify reproductive isolation in sympatry through long-distance mating signals. Female preference for their own song type has been established as a strong pre-mating reproductive barrier, but the potential existence of additional isolating mechanisms has not been investigated. We quantify divergence in cuticular lipid profiles and external genital structures between song types. These traits show significant divergence among species of Orthoptera and are known to be used in mate recognition following contact. We show that divergence among sympatric Mecopoda song types in both cuticular lipid profiles and two external genital structures is sufficiently extensive that either of them can be used to identify individual song type with 90% accuracy. Our findings suggest that multiple isolating mechanisms are likely to evolve simultaneously to facilitate a more robust reproductive isolation. This indicates a role for sexual selection in the divergence and potential future speciation of these populations and suggests that reproductive isolation may frequently evolve through simultaneous divergence across different aspects of mate recognition systems.